Associations of screen time, sedentary time and physical activity with sleep in under 5s: A systematic review and meta-analysis. (February 2020) - Janssen, Xanne; Martin, Anne; Hughes, Adrienne R.; Hill, Catherine M.; Kotronoulas, Grigorios; Hesketh, Kathryn R.
Summary: Sleep is crucial to children's health and development. Reduced physical activity and increased screen time adversely impact older children's sleep, but little is known about these associations in children under 5 y. This systematic review examined the association between screen time/movement behaviors (sedentary behavior, physical activity) and sleep outcomes in infants (0–1 y); toddlers (1–2 y); and preschoolers (3–4 y). Evidence was selected according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and synthesized using vote counting based on the direction of association. Quality assessment and a Grading of Recommendations, Assessment, Development and Evaluation was performed, stratified according to child age, exposure and outcome measure. Thirty-one papers were included. Results indicate that screen time is associated with poorer sleep outcomes in infants, toddlers and preschoolers. Meta-analysis confirmed these unfavorable associations in infants and toddlers but not preschoolers. For movement behaviors results were mixed, though physical activity and outdoor play in particular were favorably associated with most sleep outcomes in toddlers and preschoolers. Overall, quality of evidence was very low, with strongest evidence for daily/evening screen time use in toddlers and preschoolers. Although high-quality experimental evidence is required, our findings should prompt parents, clinicians and educators to encourage sleep-promoting behaviors (e.g., less evening screen time) in the under 5s.